1982
DOI: 10.1038/bjc.1982.240
|View full text |Cite
|
Sign up to set email alerts
|

Vascular structure of five human malignant melanomas grown in athymic nude mice

Abstract: Summary.-The vascular structure of 5 human malignant melanomas grown in athymic nude mice was characterized. The vessels were filled with a radio-opaque medium administered via the abdominal aorta of the mice. X-ray images, obtained from 720gum-thick tumour sections, provided qualitative information on the vascular structure of the tumours. Histograms for vessel length, surface, and volume as a function of vessel diameter were obtained by stereological analysis of 2,um-thick sections. The volume fraction of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 15 publications
4
33
1
Order By: Relevance
“…Fraction of cells in S-phase and DNA-index were calculated from DNA-histograms obtained by flow cytometry (Lindmo & Steen, 1977;Rofstad et al, 1982). Vascular parameters were determined by stereological analysis of histological sections from tumours whose vascular system was filled with a contrast medium (Solesvik et al, 1982). Results and discussion Variability in radiation response Growth curves for irradiated and unirradiated tumours are presented in Figure 1.…”
Section: T12-t2 T2mentioning
confidence: 99%
See 1 more Smart Citation
“…Fraction of cells in S-phase and DNA-index were calculated from DNA-histograms obtained by flow cytometry (Lindmo & Steen, 1977;Rofstad et al, 1982). Vascular parameters were determined by stereological analysis of histological sections from tumours whose vascular system was filled with a contrast medium (Solesvik et al, 1982). Results and discussion Variability in radiation response Growth curves for irradiated and unirradiated tumours are presented in Figure 1.…”
Section: T12-t2 T2mentioning
confidence: 99%
“…The studies have been concentrated on 5 different lines of xenografts of similar histology, which originated from tumours in 5 different patients. These xenograft tumour lines show individuality with respect to: characteristic growth patterns ; vascular structures (Solesvik et al, 1982); and, X-ray survival curves following irradiation in vitro (Rofstad & Brustad, 1981 Five different human melanomas (E.E., E.F., G.E., M.F., V.N. ), which each were derived from metastases of patients at The Norwegian Radium Hospital, were studied in the present work.…”
mentioning
confidence: 99%
“…Animal experiments suggest that there is a proportionate increase in the neovascularisation of melanoma with progressive tumour growth (Solesvik et al, 1982). We have previously shown that thick melanomas have greater vascularity than thin lesions (Srivastava et al, 1986b).…”
mentioning
confidence: 99%
“…and the R.A. melanomas. The origin and some biological characteristics of this xenograft have been reported previously (Rofstad et al, 1980;Solesvik et al, 1982). The E.E.…”
Section: Resultsmentioning
confidence: 57%